(untitled) (Minang Chemistry Journal (MCJ), 2026)
This study reports the rapid green synthesis of silver nanoparticles (AgNPs) using Moringa oleifera leaf extract as a reducing and stabilizing agent. The synthesized nanoparticles were characterized using UV-Vis spectroscopy, XRD, and TEM. The UV-Vis spectrum showed a characteristic surface plasmon resonance peak at 420 nm. The AgNPs exhibited significant antibacterial activity against E. coli and S. aureus, making them promising candidates for bio-medical applications.